If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 = 8(x + 5) + -8 Reorder the terms: 96 = 8(5 + x) + -8 96 = (5 * 8 + x * 8) + -8 96 = (40 + 8x) + -8 Reorder the terms: 96 = 40 + -8 + 8x Combine like terms: 40 + -8 = 32 96 = 32 + 8x Solving 96 = 32 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 96 + -8x = 32 + 8x + -8x Combine like terms: 8x + -8x = 0 96 + -8x = 32 + 0 96 + -8x = 32 Add '-96' to each side of the equation. 96 + -96 + -8x = 32 + -96 Combine like terms: 96 + -96 = 0 0 + -8x = 32 + -96 -8x = 32 + -96 Combine like terms: 32 + -96 = -64 -8x = -64 Divide each side by '-8'. x = 8 Simplifying x = 8
| -5(x+2)=3(x-4) | | 2ydx-3xdy=0 | | 5x-2(x-6)=2x+2(x-1) | | 2x+3(6x)=40 | | log(x+5)-log(x+3)=2 | | 198=L(x+2)2 | | -3z^2-8z+1=0 | | 4/5:13/10 | | (5-3e^2)/(e^2-1) | | 0.7-0.2x=6.1 | | 7-3(x+1)=x-3(x-1) | | 13.8-9/10 | | Y=100-4x^2 | | 2(3y)+3y=45 | | f(x)=-3(x-4)(x+5) | | 6x+5x=3x+22x-54 | | 15-(2x-1)=8-(2-3) | | 6x+5x=6x+28-2x | | y^2dx-(2xy+3)dy=0 | | 10-3f=40 | | 115-(2x-1)=8-(2-3x) | | -5a(a+6)= | | -57+-21= | | 3(x+4)2-7=20 | | 1.5=3.8x^4+4.4x^3 | | y=42000-8.6(10) | | 11x-3=-58 | | f(x)=8ln(6x) | | (X+12)(x-8)=0 | | 2x-24+4x+6=180 | | 2x+5x-1+90=180 | | 5x+20+3x+66+x+x=360 |